History of the Proffesorship of Pharmacology of the Faculty of Medicine of the University of Valladolid (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
In the first part of this work, the teaching, research and management work of the full professors of the Proffesorship of Pharmacology during the period 2002-2014 is presented.  In the second part, the biography of the full professors of the Chair of Pharmacology of the University of Valladolid during the period 1979-2014 is briefly summarized.